2013
DOI: 10.1007/s10840-013-9841-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pulmonary vein isolation ablation for paroxysmal atrial fibrillation: predictive role of left atrial mechanical dyssynchrony by speckle tracking echocardiography

Abstract: Speckle tracking strain analysis echocardiography can evaluate the LA mechanical dyssynchrony quantitatively. The severity of LA mechanical dyssynchrony by VVI can predict the outcome of PVI catheter ablation for paroxysmal AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The LA mechanical dyssynchrony, which clearly indicates the presence of atrial structural and electrical remodeling, can predict recurrence of AF after CA in patients with paroxysmal AF [40,41].…”
Section: Left Atrial Mechanical Dyssynchronymentioning
confidence: 99%
See 1 more Smart Citation
“…The LA mechanical dyssynchrony, which clearly indicates the presence of atrial structural and electrical remodeling, can predict recurrence of AF after CA in patients with paroxysmal AF [40,41].…”
Section: Left Atrial Mechanical Dyssynchronymentioning
confidence: 99%
“…Loghin at al. [40], used an algorithm based on 2D-STE -the vector velocity imaging (VVI) and looked at the timing of peak longitudinal strain obtained on opposing LA walls during atrial contractile phase. They found that maximum opposing walls delay of over 51 ms predicted AF recurrence after CA with 89% sensitivity and 72% specificity.…”
Section: Left Atrial Mechanical Dyssynchronymentioning
confidence: 99%
“…Left atrial (LA) enlargement is a well established association with AF, its complications and recurrence after CA (Lo et al, 2009;W ojcik et al, 2015). Other LA structure and function parameters, measured by echocardiography, have also been shown to predict recurrence of AF after CA (Khurram et al, 2016;Loghin et al, 2014;Park et al, 2014;Stabile et al, 2017;Zakrzewska-Koperska et al, 2014), with various accuracies. However, the exact role of LA structure and function measurements in predicting recurrence of AF after CA remains discordant.…”
Section: Introductionmentioning
confidence: 99%
“…Several predictors of AF recurrence after ablation have been identified, including age, AF type, duration of AF episodes, hypertension, and echocardiographic parameters, after cardioversion and catheter ablation (4-7). Indexed minimal left atrial (LA) volume (8), LA pressure (9), and LA mechanical dyssynchrony (10) are other factors that help to predict the success of AF ablation procedure. Several other non-invasive methods, including signal-averaged electrocardiogram (SAECG), have been used to predict the success or failure of PV ablation for AF (11-14).…”
mentioning
confidence: 99%
“…Supported by a very accurate echocardiographic investigation, the study by Salah et al (15) contributes to the comprehensive interpretation of the results of a vast number of prior attempts to predict AF recurrence after PV isolation. However, in contrast to speckle tracking technology, Doppler methodology is angle-dependent and difficult for strain measurements (10). In this respect, this study also points out the need for analyzing to what extent the information provided by Doppler methodology can be used to predict recurrence of AF after PV isolation.…”
mentioning
confidence: 99%